New developments in the management of overactive bladder: focus on mirabegron and onabotulinumtoxinA - Andersson KE (Dove Medical Press, 2013)
Karl-Erik Andersson Institute of Regenerative Medicine, Wake Forest University School of Medicine, and Department of Urology, Wake Forest Baptist Medical Center, Winston Salem, NC, USA Abstract: In the last few years, much new information has been generated on the pathophysiology, possible therapeutic targets, and pharmacologic treatment of overactive bladder (OAB). Antimuscarinic drugs are still first-line pharmacologic treatment for OAB and often have good initial response rates, but adverse effects and decreasing efficacy cause long-term compliance problems, prompting a search for new therapeutic alternatives. Mirabegron and onabotulinumtoxinA, two drugs with different mechanisms of action, and with adverse effect profiles different from those of antimuscarinics, were recently approved for treatment of OAB. However, their place in the treatment of this disorder has not yet been established. In this short review, the mechanisms of action, clinical efficacy, and safety profiles of these drugs are discussed and compared with those of the current gold standard, antimuscarinic agents. Keywords: antimuscarinics, mirabegron, onabotulinumtoxinA